CD1c-Related DCs that Express CD207/Langerin, but Are Distinguishable from Langerhans Cells, Are Consistently Present in Human Tonsils - De Monte, Anne; Olivieri, Charles-Vivien; Vitale, Sébastien; Bailleux, Sonanda; Castillo, Laurent; Giordanengo, Valérie; Maryanski, Janet L.; Segura, Elodie; Doglio, Alain (Frontiers in Immunology, 2016)
Several subsets of dendritic cells (DCs) are present in the oropharyngeal tonsillar tissues and are thought to behave as major actors in development and regulation of immunity by acting as a first line of recognition for airborne and alimentary antigens. We previously discovered in human adult tonsils infected with Epstein-Barr Virus (EBV) a subset of DCs that expressed langerin/CD207, a lectin usually recognized as a hallmark of epidermal Langerhans cells (LCs). In the present study, we analyzed the content of several child and adult tonsils in order to characterize in more detail the phenotype of these tonsillar CD207-expressing DCs (tCD207 DCs) and to compare it with that of other human DC subsets. We showed that all the human tonsils studied (n=12) contained significant proportions of tCD207 DCs among tonsillar cells expressing HLA-DR. Moreover, the presence of tCD207 DCs in tonsils from young children free of EBV infection indicated that these cells could be established early in the tonsil independently of EBV infection. We also showed that tCD207 DCs, that were found mainly located within the tonsillar lymphoid stroma, were distinguishable from LCs by the level of expression of CD1a and EpCAM, and also from human inflammatory DCs (infDCs) by the lack of CD1a, CD206 and CD14 expression. Detailed analysis of cell surface DC markers showed that tCD207 DCs were unrelated to CD141+ DCs or macrophages, but defined a subtype of tonsillar DCs closely related to myeloid resident CD1c DCs. Since it was established that blood CD1c myeloid DCs exhibit plasticity and are capable of expressing CD207 notably in the presence of inflammatory cytokines, it is tempting to speculate that CD207+ CD1c+ DCs may play a specific immune role.